A fisioterapia na atenção primária do idoso: uma revisão da literatura - Silva, Ana Paula Gonçalves da (2005)
The present study, of literature review, of a descriptive-exploratory nature, aimed to compile the information obtained from the literature about physiotherapy in primary care of the idode, highlighting the concordant and conflicting aspects on the theme. The places where the professional works in relation to the primary care of the elderly were not taken into consideration, but whether there is a real participation by them in this level of care, with the elderly population. Therefore, it was possible to go through the history of primary health care and the controversy that exists when trying to conceptualize it. By involving this level of care and the professional physiotherapist, the current researched literature demonstrates that very little he acts, and that his participation has been more linked to the secondary and tertiary levels. When inserting the elderly into this context, it was possible to perceive, through studies, that physical therapy in primary care, specifically involving this population is very needy and is still in a construction process. Therefore, when a literature review was carried out with updated scientific papers on this subject, it was possible to indicate the need for greater possibilities that emerge from the participation of physiotherapy. This professional must be a member of a health care team involving the elderly, guiding and encouraging physical activities. Whenever necessary, serve as a gateway to the system, being the first contact professional, allowing the inclusion of the elderly in the health system, with a view to improving the quality of life of this portion of the population.